Juridical Study of Digital Campaign Regulations and Election Violations in the 2024 Elections in Indonesia: Analysis of the Role of the ITE Law in Handling Hoaxes and Hate Speech - Khuan, Hendri; Wahyudi, Fajar Satriyawan (West Science Law and Human Rights, 2025)
This study examines the role of the Information and Electronic Transactions (ITE) Law in regulating digital campaigns and addressing election violations during the 2024 Indonesian elections. With the increasing prevalence of online hoaxes and hate speech, this research adopts a normative juridical approach to analyze the effectiveness and limitations of the ITE Law in maintaining electoral integrity. The study reveals that while the ITE Law has provided a legal framework for addressing digital violations, challenges in its enforcement, such as vague provisions, selective implementation, and jurisdictional issues, have undermined its impact. The research also compares Indonesia's approach with international practices and suggests improvements in legal clarity, proactive monitoring, enforcement, public awareness, and international cooperation. The findings contribute to the development of a more robust regulatory framework for future elections in Indonesia, aiming to strengthen the role of digital platforms in promoting fair and transparent elections.